The influence of work discipline, motivation, and work environment on the performance of employees - Louis Brancourt; Budi Shantika; Caren Angellina Mimaki (Universitas Pendidikan Nasional, 2022)
This study aimed to determine the effect of work discipline, motivation, and work environment on employee performance PD (Perusahaan Daerah) Pasar Kota Denpasar. This research was a quantitative study that described and explained the influence of work discipline, motivation, and work environment on employee performance PD Pasar Kota Denpasar. The study population was all employees working at PD Pasar Kota Denpasar, amounting to 130 employees using sampling techniques with 65 employee respondents. Data collection techniques that the authors used in this study include the test instrument, classic assumption test, multiple linear regression, coefficient of determinant (R²), t-test, and f-test. The results of the analysis showed that (1) Work discipline had a positive and significant effect on the performance of PD Pasar Kota Denpasar with a significant value of 0,021. (2) Work motivation had a positive and significant effect on the performance of PD Pasar Kota Denpasar with a significant value of 0,000. (3) The work environment had a positive and significant effect on the performance of PD Pasar Kota Denpasar with a significant value of 0,009. (4) Work discipline, motivation and work environment on employee performance together had a positive and significant effect on employee performance with a significant value of 0,000 less than 0,05, the hypothesis was accepted.